The CORE‐10: A short measure of psychological distress for routine use in the psychological therapies. Issue 1 (26th February 2013) - Barkham, Michael; Bewick, Bridgette; Mullin, Tracy; Gilbody, Simon; Connell, Janice; Cahill, Jane; Mellor-Clark, John; Richards, David; Unsworth, Gisela; Evans, Chris
Abstract: Background : There is a need for a generic, short, and easy‐to‐use assessment measure for common presentations of psychological distress in UK primary care mental health settings. This paper sets out the development of the CORE‐10 in response to this need. Method : Items were drawn from the CORE‐OM and 10 items were selected according to a combination of usefulness, coverage of item clusters, and statistical procedures. Three CORE‐OM datasets were employed in the development phase: (1) a primary care sample, (2) a sample from an MRC platform trial of enhanced collaborative care of depression in primary care, and (3) a general population sample derived from the Office of National Statistics Psychiatric Morbidity Follow‐up survey. A fourth dataset comprising a sample from an occupational health setting was used to evaluate the CORE‐10 in its standalone format. Results : The internal reliability (alpha) of the CORE‐10 was .90 and the score for the CORE‐10 correlated with the CORE‐OM at .94 in a clinical sample and .92 in a non‐clinical sample. The clinical cut‐off score for general psychological distress was 11.0 with a reliable change index (90% CI) of 6. For depression, the cut‐off score for the CORE‐10 was 13 and yielded sensitivity and specificity values of .92 (CI=.83–1.0) and 0.72 (CI=.60–.83) respectively. Conclusion : The CORE‐10 is an acceptable and feasible instrument that has good psychometric properties and is practical to use with people presenting with common mental health problems in primary care settings.